help to solve this problem
Attachments:
![](https://hi-static.z-dn.net/files/df8/7f8f09ed7ad6d8d1b2c999475ad4c8e8.jpg)
Answers
Answered by
1
Answer:
Given : AC = BD
To Prove : AB = CD
Step-by-step explanation:
Proof : AC = AB + BC ( From the figure )..........(1)
BD = BC + CD ( From the figure ).........(2)
AC = BD ( Given ).................................….(3)
By Substuting equation (1) and (2) in (3),
AB + BC = BC + CD
AB + BC - BC = CD
AB + CD
Hence, proved.
Hope it helps.
Plz mark brainliest answer
Similar questions